PENGARUH PERMINTAAN DAN HARGA BARANG SUBSTITUSI TERHADAP PENDAPATAN PEDAGANG IKAN BANDENG DI KOTA LHOKSEUMAWE - Devi Andriyani; Nurzaitun Nurzaitun; Asnawi Asnawi; Syarifah Safira; Siti Aisyah Barunea (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study aimed to determine the influence of demand and price of substituted goods on the income of milkfish sellers in Lhokseumawe City. The data used in this study are primary data obtained from surveys. The data analysis method used in this study is the Multiple Linear Regression Model. The variables studied are free from the classical assumption tests. The results simultaneously show that the demand and price of substituted goods positively and significantly influenced the income of milkfish sellers in Lhokseumawe City. This study obtained the value of the coefficient of determination (R2) of 0,433580 or 43.3580%, which had a significant effect on the income of milkfish traders in Lhokseumawe City.